1983
DOI: 10.1039/c39830001497
|View full text |Cite
|
Sign up to set email alerts
|

[CH3COH]˙+, the central intermediate in the isomerization–dissociation reactions of ionized vinyl alcohol

Abstract: In complete agreement with experimental results ab initio molecular orbital calculations predict that ionized hydroxy(methyl)carbene, [CH,COH] +, does not only exist as a stable C,H,O*+ isomer but also serves as the key intermediate in the isomerization-dissociation processes of the cation radical of gaseous vinyl alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 1 publication
0
10
1
Order By: Relevance
“…We investigated the cationic surface computationally, revealing a mechanism by which, even upon 10.5 eV photoionization, the parent CH 3 C(O)CH 2 radical could dissociatively ionize to C 2 H 5 + + CO; this occurred via an isomerization and subsequent dissociation on the cationic surface. This mechanism is quite different from other situations where, at low enough energies, photoionization could result in detection at the parent mass-tocharge ratio [13][14][15]. In our case, there is no local minimum at the CH 3 C(O)CH 2 + cation's isomer, so a near-barrierless isomerization occurs.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…We investigated the cationic surface computationally, revealing a mechanism by which, even upon 10.5 eV photoionization, the parent CH 3 C(O)CH 2 radical could dissociatively ionize to C 2 H 5 + + CO; this occurred via an isomerization and subsequent dissociation on the cationic surface. This mechanism is quite different from other situations where, at low enough energies, photoionization could result in detection at the parent mass-tocharge ratio [13][14][15]. In our case, there is no local minimum at the CH 3 C(O)CH 2 + cation's isomer, so a near-barrierless isomerization occurs.…”
Section: Discussioncontrasting
confidence: 48%
“…Others exhibit dissociative ionization when there is a local minimum near the vertical geometry, but the internal energy of the cation is sufficiently high to allow isomerization on the cationic surface and subsequent dissociation (see Refs. [13][14][15] for a few examples). Dissociative ionization at very low photoionization energies, as investigated here, is much less common.…”
Section: Introductionmentioning
confidence: 98%
“…(Such arrangements are known to involve an appre ciable energy barrier; e.g., the CH 2CHOH+ ' to CH 3COH +' transformation requtres s 240 k] mol " ! [22].) As will be seen in the continuing discussion , this ion plays an important role on the potential energy surface shown in Figure 1, and so we will next describe the mass spectral characteristics of ionized I-methoxypropene, 2.…”
Section: T53mentioning
confidence: 99%
“…[2][3][4][5][6] Collision partners can substantially lower the barriers, however, and van der Rest et al 7 have recently reported an elegant experimental and theoretical study of the catalyzed keto-enol isomerization in thermal energy collisions with methanol. [2][3][4][5][6] Collision partners can substantially lower the barriers, however, and van der Rest et al 7 have recently reported an elegant experimental and theoretical study of the catalyzed keto-enol isomerization in thermal energy collisions with methanol.…”
Section: Introductionmentioning
confidence: 99%